RELATION BETWEEN THE SPECIAL RADAR ECHO FROM WITHIN THE ICE SHEET AND THE CONFIGURATION OF THE GROUND (I) - ホシヤマ, ミツオ; ニシツジ, アキラ; ニシオ, フミヒコ; ワダ, マコト; ワタナベ, オキツグ; HOSHIYAMA, Mitsuo; NISHITSUJI, Akira; NISHIO, Fumihiko; WADA, Makoto; WATANABE, Okitsugu (National Institute of Polar Research, 1990)
P(論文) It has been considered very difficult to analyze radar echos except for those of standard form. In this work we have attemped to estimate ground structures under an ice sheet using nonstandard radar echos. We determined the standard radar echo from the thick ice sheet and ground of the Antarctic Continent under it, and succeeded in simulating nonstandard radar echos. We have calculated the discrepancy from a standard radar echo by a simulation method, and estimated the influence of cracks and of the temperature profile within the ice sheet, volcanic ash and meteorites in the ice sheet, and shape and water content of the boundary between ice sheet and ground of the Antarctic Continent. As the gradients of temperature and density of the ice sheet are very small, the radar echo is not influenced by these within an ice sheet up to at 350-600m thick. We succeeded in estimating the shape, temperature and roughness of the ground under the ice sheet. departmental bulletin paper